1991
DOI: 10.1111/j.1751-0813.1991.tb03157.x
|View full text |Cite
|
Sign up to set email alerts
|

Left‐side displacement of the abomasum in dairy cows at pasture

Abstract: The presentation of approximately 40 dairy cows affected with left-side displacement of the abomasum (LDA) per annum in a cattle practice in East Gippsland, Victoria provided an opportunity to conduct a survey and case-control study of the disease in a grazing environment. The study, involving 37 dairy cows at pasture, revealed significant differences from the pattern of the disease occurring in the northern hemisphere where cows in older age groups, of larger frame size, higher production and fed high grain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 5 publications
3
16
0
3
Order By: Relevance
“…Most observed clinical findings were previously recorded by Jubb et al (1991) and El-Attar et al (2007). Cows with displacement showed less frequent defecation with scanty feces (Radostits et al, 2007) because the obstructed abomasum cause delaying the emptying its content (Zadnik 2003 andEl-Attar et al, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Most observed clinical findings were previously recorded by Jubb et al (1991) and El-Attar et al (2007). Cows with displacement showed less frequent defecation with scanty feces (Radostits et al, 2007) because the obstructed abomasum cause delaying the emptying its content (Zadnik 2003 andEl-Attar et al, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Shaver et al (1997) reported that from 80 to 90% LDA cases are diagnosed in the first month after calving, and Constable et al (1992) stated that the period of greater risk of suffering LDA is the first month after calving. Some authors report that first lactation is a period with high risks of LDA developing, which can happen due to probable low level of social integration of the calf, and the nutritional adaptation (Jubb et al, 1991). Mean age of the animals with LDA was 4.63±2.33 years old, i.e., relatively young animals, with low level of lactations (2.95±1.9).…”
Section: Resultsmentioning
confidence: 99%
“…Other authors report that the first lactation is also a period with relative high risks for development of DA. This can be a result of a poor social and nutritional adaptation of the newly lactating heifer [33]. Lacasse et al found a four times higher risk for DA in heifers that were fed ad libitum in the period of 1 to 1.5 years of age [37].…”
Section: Species Breed Gender Age and Production Levelmentioning
confidence: 99%